The independence left by a divided nation (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The formal independence of the Spanish empire did not bring as a consequence the unity of the political forces in the territorial demarcation of Nicaragua, the political groups of the moment did not know how to live up to what the historical moment demanded and with those opposing positions would mark a continuous scenario of conflicts and disputes that hindered the greatest progress that the country could have in the first half of the nineteenth century. The certainty of being before a transcendent historical moment and constitutive of a new relationship of political power that demanded, not only to configure and structure a set of different administrative institutions, typical of the emerging statehood, was limited in immediate practice to the rupture of the colonial bond as a result of prevailing in the leading groups, substantially local loyalties.
Keywords: Bicentennial; Independence; political power